Transport Properties of Evaporative Cooling in a Seashell Packed Bed Cooling Tower - Amalina Syahirah Binti Amir Kusin (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To investigate the physical properties of seashell as packing material. To compare the performance of cooling tower using seashell and High Density Polyethylene (HPDE) pipe as packing material. To investigate the effect of circulation rate and water to air ratio on heat and mass transfer properties of cooling tower.